ENT 530 Social Media Portfolio: PENDI / Muhammad Syafiq Ruzi - Ruzi, Muhammad Syafiq (2021)
Starting a business for PENDI products is stickers, which is to produce more stylish, funky, and even black metal sticker designs. With the existing advantages, by striving to grow the business, PENDI's business produces new products, namely t-shirts to be used as a place to develop the brand by producing a simple, stylish, dark style and also a variety of unique design concepts. When I'm starting in this business as a graphic design freelance, which makes service design in logo branding, social media design, poster advertising, and else. With my advantages in design, and start to take point to grow the business with SR GRAPHIC DESIGNER to introduces new services, to focus on one scope service design is a 2D and 3D advertising design. It means to develop some ads design to look more futuristic and creative combination designs in 2D and 3D visualization. It was established in 2019, while still studying at UiTM Kota Samarahan. This business is established in 2017 when I'm still studying diploma graphic design at POLITEKNIK MUADZAM SHAH. and doing part-time as graphic design freelance until now. Lastly, with these opportunities, i already have now, Insyaallah my business will expand in terms of marketing strategy and design to attract more customers. the pretext of wanting to focus on other careers first. Finally, with the opportunities available no